2013
DOI: 10.4172/2155-9600.1000188
|View full text |Cite
|
Sign up to set email alerts
|

The Preservative Effects of Two Local Nigerian Spices on the Shelf Life of fried Bean Cake Snacks

Abstract: Spices and herbs have been reported to be potent sources of natural antioxidants. Spices are known to impact flavour and improve overall organoleptic quality of foods. The use of naturally occurring materials like spices as preservatives has been proved to be a promising alternative to the use of chemicals. The effects of Aframomum danielli and Zingiber officinale crude extract on the storability of fried bean cake snacks were investigated. Proximate and sensory analyses of the snack were also assessed. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The result showed that there was reduced microbial load on the treated samples compared with the untreated sample at ambient temperature. Similar findings have been reported by Adedeji and Ade-Omowaye (2013) for fried beans cake. After 48-hour of production, the bacteria load of the untreated fura sample increased more than 10fold to a population of 382 x 10 5 cfu/g.…”
Section: Resultssupporting
confidence: 92%
“…The result showed that there was reduced microbial load on the treated samples compared with the untreated sample at ambient temperature. Similar findings have been reported by Adedeji and Ade-Omowaye (2013) for fried beans cake. After 48-hour of production, the bacteria load of the untreated fura sample increased more than 10fold to a population of 382 x 10 5 cfu/g.…”
Section: Resultssupporting
confidence: 92%